UiTM Environmental Sustainability Report 2023 - UiTM, UGC (UiTM Green Centre, 2023)
The Universiti Teknologi MARA Environmental Sustainability Report (ESR) 2023 is part of UiTM Green Centre’s (UGC) deliverables from the ideation of UiTM Greenation Strategic Plan. The theme for this year is ‘Greening UiTM’. The UiTM ESR 2023 summarizes the overall progress in the university and campus sustainability initiatives throughout the year which aim to be associated with the UGC Core Area – UI GreenMetric and Low Carbon Cities 2030 Challenge (LCC2030C). This report presents information on sustainable initiatives undertaken by UiTM in its main as well as branch campuses throughout the country. The UiTM community has developed value-driven sustainability perspectives as per the 17 Sustainable Development Goals and UiTM Strategic Planning 2025. UiTM has stayed the course on various initiatives to cope with the changes. This progress has presented the UiTM family with the opportunity to look for supportive collaborators and partners to learn from one another, develop creative plans, and tackle sustainability issues on the university campus, national, and international levels.